Co-harboring of Novel blaKPC–2 Plasmid and Integrative and Conjugative Element Carrying Tn6203 in Multidrug-Resistant Pseudomonas aeruginosa - Cai, Heng; Zhu, Yiwei; Hu, Dandan; Li, Yue; Leptihn, Sebastian; Loh, Belinda; Hua, Xiaoting; Yu, Yunsong (Frontiers in Microbiology, 2021)
Many strains of the opportunistic pathogen Pseudomonas aeruginosa have acquired resistance to multiple antibiotics. Carbapenem-resistant P. aeruginosa strains pose a global health care problem due to limited therapeutic options for the treatment of infections. The exchange of plasmids and integrative and conjugative elements (ICEs) are frequently used to facilitate antibiotic-resistance gene acquisition. In our study, four strains of P. aeruginosa were isolated from the same patient in a tertiary referral hospital in China, with one of them displaying different resistance to aminoglycoside antibiotics. In this strain P33, we observed an immobile plasmid pP33-2 carrying a novel blaKPC−2 gene segment (ISKpn27-blaKPC−2-ISKpn6-korC-ORF-klcA-IS26), which we concluded to have been formed by IS26-mediated gene cluster translocation. In addition, by comparing the chromosomes of the P. aeruginosa strains that belong to the same sequence type, we identified an integrative and conjugative element, ICEP33, adjacent to a prophage. The attL site of ICEP33 is identical to the terminal part of the attR site of the prophage. The ICEP33 element contains the transposon Tn6203, which encodes antibiotic and metal resistance genes. The insertion of ICEP33 in the chromosome mediates drug-resistance of the strains to multiple antibiotics. Our study contributes to the understanding of the acquisition of antibiotic resistance in P. aeruginosa facilitated by mobile genetic elements.